Hypertension in Cape Town clothing industry clinics: Does treatment match risk? - Sephton_E_A (Centre for Infectious Disease Epidemiology and Research (CIDER), 2017)
Background: The management of hypertension according to the patient' s absolute risk of cardiovascular disease. rather than their blood pressure in isolation from other risk factors, is now widely advocated because it targets treatment at those with most to gain. In South Africa blood pressure is traditionally managed according to the patient's level of blood pressure. Main Objective: To identify the proportion of traditionally treated hypertensive patients who may benefit from cessation or intensification of treatment as judged by a risk-based approach to their management. Design: A cross sectional descriptive survey of patients and their medical records with assessment of absolute risk of cardiovascular disease using Framingham risk equations. Setting: Eight Clothing Industry Health Benefit Fund clinics in Cape Town, South Africa. Participants: 382 women and men, predominantly coloured, attending for the treatment of hypertension Main outcome measure: The proportions of patients in whom the predicted risk of a cardiovascular event within 5 years is less than 10% and those in whom the risk within five years is greater than 20%. Results: 65% of participants (CI 60 - 70%) were at less than 10% risk of a cardiovascular event in the next 5 years and 19% (Cl 15-23%) were at more than 20% risk of a cardiovascular event despite current treatment. 5% (CI 3.2-7.9%) were at greater than 20% risk of a cardiovascular event in the next 5 years having no previous history of a cardiovascular event. 14% (CI 10-17%) were at greater than 20% risk of a cardiovascular event in the next 5 years because of a previous history of a cardiovascular event. 1.3% (CI 0.4-3%) were at less than 10% risk of a cardiovascular event within the next 5 years, despite having a systolic blood pressure over 170mmHg. Conclusion: Assessment of the cardiovascular risk of patients treated for hypertension identifies those patients at most and least risk. Resources could therefore be targeted at those with the most to gain from treatment and the unwanted side effects of antihypertensive medication avoided in those at low risk. Almost two thirds of patients currently being treated for hypertension were at less than 10% risk of developing a cardiovascular event within the next 5 years. A trial of medication reduction or cessation in this group is justified and the resources could be redirected at those 5% whose risk remains very high despite current levels of treatment.